2015
DOI: 10.2105/ajph.2014.302221
|View full text |Cite
|
Sign up to set email alerts
|

A Water Availability Intervention in New York City Public Schools: Influence on Youths’ Water and Milk Behaviors

Abstract: Objectives. We determined the influence of “water jets” on observed water and milk taking and self-reported fluid consumption in New York City public schools. Methods. From 2010 to 2011, before and 3 months after water jet installation in 9 schools, we observed water and milk taking in cafeterias (mean 1000 students per school) and surveyed students in grades 5, 8, and 11 (n = 2899) in the 9 schools that received water jets and 10 schools that did not. We performed an observation 1 year after implementation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 16 publications
1
59
0
2
Order By: Relevance
“…2934 Taken together, these findings suggest that schools can use a range of strategies to make it easier for students to drink more water, and that simple modifications to the school’s drinking water environment can have a significant impact. Although previous research has shown higher-cost strategies to be effective (i.e., purchasing reusable water bottles 30 and updated water fixtures 29,33,34 ), this study shows that simply providing cups—a strategy costing less than one tenth of a cent per student each day—can increase student water intake and the prevalence of water consumption.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…2934 Taken together, these findings suggest that schools can use a range of strategies to make it easier for students to drink more water, and that simple modifications to the school’s drinking water environment can have a significant impact. Although previous research has shown higher-cost strategies to be effective (i.e., purchasing reusable water bottles 30 and updated water fixtures 29,33,34 ), this study shows that simply providing cups—a strategy costing less than one tenth of a cent per student each day—can increase student water intake and the prevalence of water consumption.…”
Section: Discussionmentioning
confidence: 94%
“…Drinking directly from fountains is simply a less-efficient strategy for drinking water. 36 Improving drinking water infrastructure, updating fixtures, and further increasing convenience, perhaps by offering tap water as a beverage on a lunch line, 34 may also be necessary for increasing water intake further. However, for districts with limited resources, simply providing cups next to existing water fountains may be an effective strategy for increasing intake and reducing water waste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The New York City Public Schools demonstrated that placing a chilled water dispenser on a school lunch line could significantly increase the proportion of students taking water as well as the amount of water consumed during lunch. 36 The Boston Public Schools tested a low-cost strategy placing promotional signage and cup-holders filled with recyclable cups next to cafeteria water fountains which led to increased student water consumption and potentially reduced sugar-sweetened beverage intake. 37 A study in Los Angeles middle schools that distributed water bottles to students along with placing promotional signage around water dispensers also saw increases in the proportion of students consuming water.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental issues are raised with respect to the use of disposable plastic bottles (131). Installing water fountains and water bottle refilling stations in public areas increases water usage (41). Distribution of reusable water bottles can motivate increased water drinking (42,116).…”
Section: Behavioral Settingsmentioning
confidence: 99%